2019
DOI: 10.1111/ipd.12488
|View full text |Cite
|
Sign up to set email alerts
|

Constipation, antiepileptic drugs, and gingivitis in children and adolescents with cerebral palsy

Abstract: Background Cerebral palsy (CP) individuals present with epilepsy, which requires the use of antiepileptic drug (AED). Hypothesis Since an inflammatory response may contribute to epileptogenesis, the hypothesis tested was that constipation would be associated with gingivitis and the use of AED in children and adolescents (CA) with CP. Design A comparative study was conducted with 101 CA aged 5‐17 years (10.8 ± 4.9), classified as constipated (G1; n = 57) or not constipated (G2; n = 44). Clinical patterns, AED u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…GMFCS is stratified into five levels of body mobility: Level I (walking without limitations), Level II (walking with limitations), Level III (walking using a hand-held mobility device), Level IV (self-mobility with limitations), and Level V (transported in a wheelchair) (6). Our previous studies demonstrated that out of 254 subjects, 50 (19.7%) had GMFCS I, II, or III while 204 (80.3%) presented GMFCS IV or V (7)(8)(9). Notably, epilepsy prevalence increases in spastic CP subjects at the highest GMFCS classifications (IV and V) (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GMFCS is stratified into five levels of body mobility: Level I (walking without limitations), Level II (walking with limitations), Level III (walking using a hand-held mobility device), Level IV (self-mobility with limitations), and Level V (transported in a wheelchair) (6). Our previous studies demonstrated that out of 254 subjects, 50 (19.7%) had GMFCS I, II, or III while 204 (80.3%) presented GMFCS IV or V (7)(8)(9). Notably, epilepsy prevalence increases in spastic CP subjects at the highest GMFCS classifications (IV and V) (10).…”
Section: Introductionmentioning
confidence: 99%
“…Constipation is caused by multiple factors including: (1) reduced intake of fiber and liquids (responsible for the digestive system functioning) (11), (2) central nervous system damage (12), (3) mobility reduction (13), (4) and/or the use of antiepileptic drugs (AEDs) (11,14). In subjects using AEDs the incidence of gut constipation is elevated (7). Other side effects co-occurring with gastrointestinal complications include oral dysbiosis, gingival bleeding (GB), and an increase of systemic inflammation (15).…”
Section: Introductionmentioning
confidence: 99%
“…The first study, which evaluated the association between intestinal constipation, use of antiepileptic drugs (AEDs), and gingivitis in subjects with spastic CP, was published by our work group (Figure 2) [35]. It was clearly demonstrated an association between intestinal constipation and the use of GABA antiepileptic drugs (phenobarbital, primidone, benzodiazepines including diazepam, lorazepam, and clonazepam; topiramate, felbamate, ezogabine); GABA transporter tiagabine GABA transaminase (vigabatrin); synaptic release machinery SV2A (levetiracetam, brivaracetam α2δ gabapentin, gabapentin enacarbil, pregabalin).…”
Section: Epilepsymentioning
confidence: 99%
“…Constipation may be caused by multiple components including: 1) reduced intake of fiber and liquids (responsible for the digestive system functioning) [13], 2) central nervous system damage [14], 3) mobility reduction [15], 4) and/or the use of AEDs [13,16]. In subjects using AEDs the incidence of constipation is elevated [7]. Other side effects co-occurring with the gastrointestinal complications include oral dysbiosis, gingival bleeding (GB), and increase of systemic inflammation [17].…”
Section: Introductionmentioning
confidence: 99%
“…GMFCS is stratified into five levels of body mobility: Level I (walks without limitations), Level II (walks with limitations), Level III (walks using a hand-held mobility device), Level IV (self-mobility with limitations) and Level V (transported in a wheelchair) [6]. Our previous studies demonstrated that out of 254 subjects, 50 (19.7%) subjects had GMFCS I, II or III while 204 (80.3%) presented GMFCS IV or V [79]. These proportion results reflect on the population of this current cohort.…”
Section: Introductionmentioning
confidence: 99%